The Effect of Compensation on Employee Performance With Motivation as Mediator at KTS Balinese Villas Canggu - Nugraha, Surya; Widhya Pibriari, Ni Putu (Jurnal Manajemen Pelayanan Hotel, 2022)
This study aims to determine the effect of compensation on employee performance at KTS Balinese Villas Canggu, through motivation as a mediator. This research is a population study, where the entire population is used as a sample of 30 people. This study uses quantitative data types and is in the form of causal associative research, namely research that aims to determine the relationship between two or more variables and this relationship has a causal nature. There are 3 (three) operational variables to be studied, namely: Compensation, Employee Performance, and Work Motivation. The research instrument testing consists of 2 (two) stages, namely the instrument validity test and the instrument reliability test. This study will analyze and explain the effect of compensation on employee performance with motivation as a mediating variable at KTS Balinese Villas Canggu. The data analysis technique used path analysis with the help of the SPSS version 17 program. The results showed that 1) Compensation had a positive and significant effect on work motivation of KTS Balinese Villas Canggu employees 2). Compensation has a positive and significant effect on the performance of KTS Balinese Villas Canggu employees 3) Motivation has a positive and significant effect on the performance of KTS Balinese Villas Canggu employees 4) Work motivation mediates the effect of compensation on the performance of KTS Balinese Villas Canggu employees. Keywords: Compensation, Motivation, Employee Performance, Mediation